Algebra-Logical Repair Method for FPGA Logic Blocks - Hahanov, V.; Galagan, S.; Olchovoy, V.; Priymak, A. (EWDTS, 2009)
At present there are many scientific publications, which cover SoC/SiP testing, diagnosis and repair problems [1-16, 19-20]. The testing and repair problem for the digital system logic components has a special place, because repair of faulty logic blocks is technologically complicated problem. Existing solutions, which are proposed in published works, can be divided on the following groups: 1. Duplication of logic elements or chip regions to double hardware realization of functionality. When faulty element is detected switching to faultless component by means of a multiplexer is carried out [4]. The FPGA models, proposed by Xilinx, can be applied for repair of Altera FPGA components. At repair the main unit of measure is row or column. 2. Application of genetic algorithms for diagnosis and repair on the basis of off-line FPGA reconfiguration not using external control devices [5]. The fault diagnosis reliability is 99%, repair time is 36 msec instead of 660 sec, required for standard configuration of a project. 3. Time-critical FPGA repairing by means of replacement of local CLBs by redundant spares is proposed in [6,7]. In critically important applications the acceptable integration level for CLB replacement is about 1000 logic blocks. The repair technologies for digital system logic, implemented on-chip FPGA, are based on existence or introduction of LUT redundancy after place and route procedure execution. Physical faults, which appear in the process of fabrication or operation, become apparent as logical or temporary failure and result in malfunction of a digital system. Faults are tied not only to the gates or LUT components but also to a specified location on a chip. The idea of digital system repairing comes to the removal of a fault element by means of repeated place and route executing after diagnosis. At that two repair technologies are possible: 1) Blockage of a defective area by means of developing the control scripts for long time place and route procedure. But it is not always acceptable for real time digital systems. The approach is oriented to remove the defective areas of any multiplicity. Blockage of the defective areas by means of repeated place and route executing results in repair of a digital system. 2) Place and route executing for repairing of real time digital systems can result in disastrous effects. The technological approach is necessary that allows repairing of the digital system functionality for milliseconds, required for reprogramming FPGA by new bitstream to remove defective areas from chip functionality. The approach is based on preliminary generation of all possible bitstreams for blocking future defective areas by means of their logical relocation to the redundant nonfunctional chip area. The larger a spare area the less a number of bitstreams, which can be generated a priori. Concerning multiple faults, not covered by a spare area, it is necessary to segment a digital project by its decomposition on disjoin parts, which have their own Place and Route maps. In this case a digital system that has n spare segments for n distributed faults can be repaired. The total chip area consists of (n+m) equal parts. The research objective is to develop a repair method for FPGA logic blocks on the basis of using the redundant chip area. Problems: 1) Development of an algebra-logical repair method for logic blocks of a digital system on basis of FPGA. 2) Development of a method for logic blocks matrix traversal to cover FPGA faulty components by spare tiles. 3) Analysis of practical results and future research.
Keywords: Algebra-Logical Repair Method; FPGA Logic Blocks